Pelatihan Guru Dalam Penggunaan Aplikasi Di Bidang Pendidikan Tingkat Sekolah Menegah Pertama Di Kabupaten Manokwari - Zulkarnain; Lilis Indrayani (AMMA : Jurnal Pengabdian Masyarakat, 2025)
Education continues to evolve with technology, especially through digital learning media in the era of revolution 4.0 and society 5.0. In particular, the development of artificial intelligence (AI), is becoming increasingly important. A training program for junior high school teachers in Manokwari Regency overcomes the challenge of limited technological capabilities. Successfully improving their skills and knowledge in utilizing digital applications to enrich the learning experience in the classroom.